2020
DOI: 10.1111/ctr.13775
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of kidney transplantation using deceased donors with history of diabetes

Abstract: Deceased diabetic kidneys are increasingly utilized in transplantation. The relationship of donor's history of diabetes to clinical and histological outcomes was examined. Forty‐nine diabetic deceased donor kidneys (D‐DM) were transplanted into 26 normal (R‐N/D‐DM) and 23 diabetic recipients (R‐DM/D‐DM) and compared to 211 diabetic recipients of normal kidneys(R‐DM/D‐N) and 466 normal recipients of normal kidneys (R‐N/D‐N). Patient survival at 5 years was 89.7% in R‐N/D‐N, 96.2% in R‐N/D‐DM, 80.1% in R‐DM/D‐N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Recently, Truong et al [ 14 ] and Khan et al [ 15 ] reported 26 diabetic donor kidney transplantations with post-perfusion biopsies and follow-up biopsies. All the donors in their study with dipstick proteinuria < 2+ (< 300 mg/g) showed diabetic lesions equal or lower than RPS IIa category on pre-implantation biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Truong et al [ 14 ] and Khan et al [ 15 ] reported 26 diabetic donor kidney transplantations with post-perfusion biopsies and follow-up biopsies. All the donors in their study with dipstick proteinuria < 2+ (< 300 mg/g) showed diabetic lesions equal or lower than RPS IIa category on pre-implantation biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The urine dipstick proteinuria or urinary protein creatinine ratio (UPCR) test may be a good screening test before pre-implantation biopsy. Truong et al [ 14 ] and Khan et al [ 15 ] reported that all their study donors with dipstick proteinuria < 2+ (< 300 mg/g) showed diabetic lesions equal or lower than RPS IIa category on pre-implantation biopsy. In our study, two donors with 2+ dipstick proteinuria were transplanted into three recipients in the biopsy proven DKD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidneys from donors with a normal creatinine on admission but an elevated creatinine at organ recovery (acute kidney injury) have graft survival comparable to kidneys from donors without poor function 11‐14 . Kidneys from donors with a history of diabetes can be used without compromising recipient outcomes 15‐17 …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Kidneys from donors with a history of diabetes can be used without compromising recipient outcomes. [15][16][17] The Kidney Donor Profile Index (KDPI) score also has limited usefulness. In 2013, 59 percent of kidneys with a KDPI > 85 were discarded 18).…”
mentioning
confidence: 99%